Line scan images of IODP Hole 389-M0103A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Collection of line scan images from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The offshore phase of this expedition took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA, followed by the onshore phase from 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. Line scan images were obtained during the onshore phase from the cleaned fresh cut surfaces directly after longitudinal splitting of core sections into work and archive halves. Images were obtained using the line scan sensor of the Avaatech Superslit X-ray fluorescence (XRF) core scanner in operation at MARUM. The line scan program of this scanner uses the Stemmer Common Vision Blox platform to acquire and process color images. Image resolution is ~150 pixel/cm in the crosscore and downcore direction. All split cores were measured using aperture setting f/11+ (a fixed value between 11 and 16). When cores were darker (e.g., in lava), the aperture was increased to up to f/5.6, and for lighter rocks (e.g., some corals) the aperture was decreased to f/13. This dataset includes the curated cropped images of working and archive halves for the best fitting aperture, respectively. File naming follows standard IODP file naming convention: Exp-SiteHole-CoreCoretype-SectionHalf. For example, a file 389-M0109A-06R-1W.jpg identifies the image of the working half of section 1, core 6R (R indicating rotary coring method), from Hole M0109A from Expedition 389. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025